Analisis Spasial Sebaran Penderita HIV Berbasis SIG di Kabupaten Banyumas - Ridho Batara; Hana Hanifa (Geography Education Study Program, Universitas Kanjuruhan Malang, 2026)
This study aims to map the spatial distribution of Human Immunodeficiency Virus (HIV) cases in Banyumas Regency using Voluntary Counseling and Testing (VCT). HIV is a virus that attacks the human immune system and remains a major public health problem. Data from the Banyumas District Health Office indicate fluctuations in the number of HIV cases, highlighting the need for spatially based mapping to support more effective control efforts. The methods used include primary data collection from VCT test results and secondary data in the form of epidemiological HIV data in Banyumas Regency for the period 2019–2023. Data were analyzed using Geographic Information Systems (GIS) with QGIS software through a classification process that categorized HIV cases into low, medium, and high classes. The results show that HIV cases are distributed across all sub-districts in Banyumas Regency, with fluctuations in case numbers and a notable increase in 2022 compared to previous years. The HIV distribution mapping provides thematic maps identifying areas with varying levels of HIV cases. These results are expected to support local governments and health institutions in determining priority intervention areas and formulating more targeted, data- based HIV prevention and control strategies in Banyumas Regency.